ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE PADA PT. BANK DANAMON INDONESIA Tbk - A, FANNY SYAFRIDA; ALKASARI, INTAN; AUDRILIA, NATASYA; LEONARDO S, NICO; PRAMUTIA, RINA; ALVIAN, SADDAM; NOVIRA SUCIPTO, TIA (JURNAL ILMIAH MAKSITEK, 2023)
This research aims to evaluate and examine how good corporate governance is implemented at PT. Bank Danamon Indonesia Tbk, a financial institution operating in Indonesia from 2020 to 2022. The method used in this research is a qualitative approach with a focus on case and descriptive studies. This research is based on collecting secondary data originating from financial reports, company websites, and previous journals. Based on the results of the research that has been carried out, it appears that PT Bank Danamon Indonesia Tbk has implemented various principles of good corporate governance well. This can also be supported by the achievements of PT Bank Danamon Indonesia Tbk, which received the title "Good" from the results of the GCG self-assessment